APPLICATION OF THE EXAMPLE NON EXAMPLE MODEL IN SOCIAL STUDIES LEARNING FOR GRADE IV STUDENTS OF ELEMENTARY SCHOOL 02 SURODADI - Mitha Natasya Putri; Aren Frima; Tio Gusti Satria (Literasi Nusantara, 2020)
The research objective was to determine the application of the Non Example Example Model in Social Studies Learning for grade IV Students of Elementary School 02 Surodadi. The research method used is Quasi Experiment. One-group research design pretest-posttest design. Data collection techniques using test techniques. The collected data were analyzed using z-test at the significant level ? = 0.05. Based on the results of the analysis using the z-test, it can be concluded that the learning outcomes of the fourth grade students of Elementary School 02 Surodadi after the application of the Example Non Example Model in social studies learning are significant. The average (x ?) score for the final test of students was 74,53 with the percentage of the number of students who had not completed it was 15% and the number of students who had completed was 85%.